TEMPORAL EVALUATION OF SURFACE WATER QUALITY AND WASTEWATER TREATMENT IN RIO CLARO-SP - Blasius, Jandir Pereira [UNESP]; Dos Santos, Paulo Henrique [UNESP]; de MORAES, Renata Xavier Lona [UNESP]; de TOLEDO, André Corrêa [UNESP]; Garcia, Marcelo Loureiro [UNESP] (UNESP - Universidade Estadual Paulista, 2022)
Considering the importance of water and the influence of human actions on the degradation of water resources, the present work aimed to evaluate temporally the quality of surface water and the sewage treatment system in the municipality of Rio Claro-SP. The water quality was evaluated at five monitoring points as well as the effluents from the Sewage Treatment Stations (STS): Flores and Conduta. The results were compared to the standards established by CONAMA Resolutions nº. 357/2005 and nº. 430/2011, CETESB Board Decision nº. 112/2013/E and State Decree nº. 8,468/1976. The historical analysis revealed that the parameters: turbidity, dissolved oxygen, nitrate, ammonia nitrogen and chlorophyll-a met the limits established by the Legislation. Meanwhile, electrical conductivity, BOD, Escherichia coli, total phosphorus, dissolved aluminum and iron and total manganese contents showed nonconformities. Regarding sewage treatment, the effluents from the STS studied complied with the Legislation for the indicators of BOD, pH and settling solids and showed high efficiency in removing BOD (> 80%) and COD (> 77%). In general, the evaluation of water quality indices revealed a strong correlation between soil characteristics, location and economic activities developed in the region.
AVALIAÇÃO TEMPORAL DA QUALIDADE DAS ÁGUAS SUPERFICIAIS E DO TRATAMENTO DE ESGOTO DE RIO CLARO-SP
Keywords: Environmental monitoring; Sanitation; Sustainable Development Goal nr 6; Water resources